What if God commanded something horrible? A pragmatics-based defence of divine command metaethics. Issue 4 (December 2021) - KREMERS, PHILIPP
Abstract: The objection of horrible commands claims that divine command metaethics is doomed to failure because it is committed to the extremely counterintuitive assumption that torture of innocents, rape, and murder would be morally obligatory if God commanded these acts. Morriston, Wielenberg, and Sinnott-Armstrong have argued that formulating this objection in terms of counterpossibles is particularly forceful because it cannot be simply evaded by insisting on God's necessary perfect moral goodness. I show that divine command metaethics can be defended even against this counterpossible version of the objection of horrible commands because we can explain the truth-value intuitions about the disputed counterpossibles as the result of conversational implicatures. Furthermore, I show that this pragmatics-based defence of divine command metaethics has several advantages over Pruss's reductio counterargument against the counterpossible version of the objection of horrible commands.